1983
DOI: 10.1002/chin.198323224
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS OF HETEROCYCLES USING 4‐OXO‐4,5,6,7‐TETRAHYDROINDOLES AS BIODYNAMIC MOLECULES

Abstract: Die aus den Tetrahydroindolonen (I) erhältlichen Derivate (III) werden nach den angegebenen Verfahren in die Verbindungen (V) bzw. (VII) übergeführt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Singh et al 230 and later Agarwal et al 231 synthesized various substituted indoles, but none of the compounds showed antiamoebic activity in axenic culture below the concentration of 62 µg/mL; at lower doses, all the compounds were found to be inactive. 2,6-Disubstituted-1(3)H-imidazo[4,5-c]carbazoles have been prepared, 232 and all the compounds showed in vitro antiamoebic activity only above 31 µg/mL.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Singh et al 230 and later Agarwal et al 231 synthesized various substituted indoles, but none of the compounds showed antiamoebic activity in axenic culture below the concentration of 62 µg/mL; at lower doses, all the compounds were found to be inactive. 2,6-Disubstituted-1(3)H-imidazo[4,5-c]carbazoles have been prepared, 232 and all the compounds showed in vitro antiamoebic activity only above 31 µg/mL.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The extant literature on the synthesis and bioactivity of pyrroloindazoles revealed that eight isomeric classes of pyrroloindazoles have so far been synthesised. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Of these, only the [2,3-g]-isomers [18][19][20][21][22][23][24][25][26][27] and the [3,2-e]-isomers 22,24,25 display various biological activities. Thus, the [2,3-g]-isomers 1-4 and the [3,2-e]-pyrroloindazole 5 were bioactive.…”
Section: Introductionmentioning
confidence: 99%
“…Among these two classes of pyrroloindazoles, only the [2,3-g]-types have already been subjected to rather thorough synthetic investigations. [18][19][20][21][22][23][24][25][26][27] But the [3,2-e]-types were synthesized only twice, neither of which was a general route.…”
Section: Introductionmentioning
confidence: 99%